Isotope-selective control of the clusterization of SF6 molecules by an IR laser during gasdynamic expansion of an SF6/Ar mixture. (31st July 2018) - Lokhman, V N; Makarov, G N; Malinovskii, A L; Petin, A N; Poydashev, D G; Ryabov, E A
Abstract: We present the results of our investigation into the isotope-selective control of the clusterization of SF6 molecules during their gasdynamic expansion in a mixture with an argon carrier gas using IR laser radiation. The method is based on the selective vibrational excitation of molecules of a chosen isotopic composition by an IR laser near the nozzle edge, which leads to the suppression of their clusterization with each other and with argon atoms. The experimental setup and the method of investigation are described. Results are presented on determining the efficiency and the selectivity of the clusterization suppression of molecules at different gas compositions above the nozzle, as well as at different distances of the irradiation region of particles from the nozzle edge. Dependences of the clusterization suppression efficiency on the frequency and power of the exciting laser radiation are obtained. Experiments on the selective suppression of the clusterization of SF6 molecules in mixtures with other carrier gases have also been performed. It is found that controlling the clusterization process of SF6 molecules in a mixture with the argon carrier gas makes it possible to achieve relatively high selectivity values. Thus, in the case of using an SF6 /Ar mixture at a 1/200 pressure ratio, the obtained selectivity of the clusterization suppression of 32 SF6 molecules with respect to 34 SF6 molecules under jet irradiation at the 10P(16) CO2 laser line (at a frequency of 947.74 cm −1 ) was . Conditions are found under which optimal values of the efficiency and selectivity of the clusterization suppression of molecules are realized.